Contributions from the person-centred experiential approach to the field of social pedagogy - Murphy, David; Joseph, Stephen (Taylor & Francis, 2018)
The aim of this article is to show how the theory and philosophy of the person-centred experiential approach, originally developed by the psychologist Carl Rogers, can usefully inform the development of professional practice, educational methods and critical social theory of social pedagogy. Social pedagogy is introduced, followed by a description of philosophical and theoretical underpinnings to the person-centred experiential approach. It is suggested that person-centred experiential theory offers a meta-theoretical basis to social pedagogy. Evidence is provided from the social pedagogy literature to support the proposed fit. It is proposed that a radical form of person-centred experiential therapy is a form of social pedagogic practice, that it is premised on a pedagogical discourse and not a mental illness discourse, and that it addresses personal and structural power, and the dialectical relation between self and society. It is concluded that person-centred experiential theory provides a foundation to social pedagogy as an emerging field of social theory, research and practice.